2020
DOI: 10.1007/s10286-020-00669-2
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability and falls in Huntington’s disease

Abstract: The funding agencies did not have a role in the development of the study, analysis of data, and writing of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 51 publications
(85 reference statements)
0
27
0
Order By: Relevance
“…Reduced cortical and subcortical blood flow and heart rate have been reported as examples of pathological abnormalities in HD hearts [ 85 , 86 , 87 , 88 ]. HD patients’ heart rate variability pattern is consistent with a higher sympathetic prevalence [ 89 ]. Further studies with HD animal models reaffirmed cardiac pathological events, such as variations in the heart rate and cardiac remodeling [ 90 , 91 , 92 ].…”
Section: Purines In Huntington’s Diseasementioning
confidence: 80%
“…Reduced cortical and subcortical blood flow and heart rate have been reported as examples of pathological abnormalities in HD hearts [ 85 , 86 , 87 , 88 ]. HD patients’ heart rate variability pattern is consistent with a higher sympathetic prevalence [ 89 ]. Further studies with HD animal models reaffirmed cardiac pathological events, such as variations in the heart rate and cardiac remodeling [ 90 , 91 , 92 ].…”
Section: Purines In Huntington’s Diseasementioning
confidence: 80%
“…It has been reported that being prone to falling is one of the strongest predictors of nursing home placement. 19 Falls and their resulting injuries are responsible for major health, social, and economic problems. A systematic review of the literature concluded that the incidence of falls in older persons follows a circadian variation.…”
Section: Search Methodologymentioning
confidence: 99%
“… 28–32 Different studies have used ANS evaluation and, in particular, heart rate variability (HRV) to detect and predict the risk of falling in various populations. 19 , 33 The identification of autonomic parameters as markers of risk of falling will help detect and monitor subjects prone to falling early on as well as allow for the implementation of preventive strategies. 34 , 35 There is no literature on the study of the circadian rhythm of the ANS, yet given the existing research on the subject and the fact that HRV is a fast, non-invasive, affordable and easily implemented technique, a 24hr HRV assessment presents and attractive and promising approach to the study of frailty and falls in older persons.…”
Section: Search Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…While there is growing evidence that CAD can manifest in OH or symptoms of orthostatic intolerance/dizziness due to baroreflex dysfunction in MS (Racosta et al, 2015 ), its relationship with falls has not received much scrutiny. Cross-sectional studies have consistently reported that, compared to age-matched healthy controls, pwMS have reduced HRV and baroreflex function (Tombul et al, 2011 ; Shirbani et al, 2018 ), both of which have been found to predict falls in patient populations characterized by dysautonomia (Castaldo et al, 2017 ; Razjouyan et al, 2017 ; Terroba-Chambi et al, 2020 ; Zanotto et al, 2020 ). A direct biological mechanism linking baroreflex dysfunction and falls can be reasonably theorized.…”
Section: Relationship Between Cad and Fallsmentioning
confidence: 99%